2008
DOI: 10.1128/aem.01473-08
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of trans C 18:1 Fatty Acids in the Rumen after Dietary Algal Supplementation Is Associated with Changes in the Butyrivibrio Community

Abstract: Optimization of the fatty acid composition of ruminant milk and meat is desirable. Dietary supplementation of algae was previously shown to inhibit rumen biohydrogenation, resulting in an altered milk fatty acid profile. Bacteria involved in biohydrogenation belong to the Butyrivibrio group. This study was aimed at relating accumulation of biohydrogenation intermediates with shifts in Butyrivibrio spp. in the rumen of dairy cows. Therefore, an experiment was performed with three rumen-fistulated dairy cows rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
136
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(161 citation statements)
references
References 37 publications
19
136
1
5
Order By: Relevance
“…The SAB fraction produced considerable amounts of C18:0 and 6 SAB clones were closely associated with the C18:0-producing branch whereas 32 SAB clones were positioned on different sub-clusters between both genera (Figure 1). Similar results were obtained in a previous experiment with dairy cows supplemented with docosahexaenoic acid-enriched algae, which dramatically decreased ruminal C18:0 production, although 20% of the clones remained clustered in close relationship with the C18:0-producing branch (Boeckaert et al, 2008).…”
Section: Effect Of Time (T) Y Interaction Between Fraction and Time supporting
confidence: 88%
See 2 more Smart Citations
“…The SAB fraction produced considerable amounts of C18:0 and 6 SAB clones were closely associated with the C18:0-producing branch whereas 32 SAB clones were positioned on different sub-clusters between both genera (Figure 1). Similar results were obtained in a previous experiment with dairy cows supplemented with docosahexaenoic acid-enriched algae, which dramatically decreased ruminal C18:0 production, although 20% of the clones remained clustered in close relationship with the C18:0-producing branch (Boeckaert et al, 2008).…”
Section: Effect Of Time (T) Y Interaction Between Fraction and Time supporting
confidence: 88%
“…Lipid extraction followed the method of Folch et al (1957) with some adaptations as described by Chow et al (2004). Methylation of fatty acids and subsequent identification of fatty acid methyl esters were performed as described in Boeckaert et al (2008).…”
Section: In Vitro Incubationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tajima et al (2001) quantified changes of up to 10 different rumen bacteria in cows with a dietary switch from hay to grain using real-time PCR technique. Boeckaert et al (2008) showed that algae feeding changed the rumen FA profile and these changes were associated with changes in the bacterial community. But the challenge remains in identifying the t10-18:1 producing bacterial species under these modified rumen conditions.…”
Section: Pufa Metabolismmentioning
confidence: 98%
“…Also, Butyrivibrio proteoclasticus has been reported to be the principal rumen bacteria involved in biohydrogenation of C18:1 FA (Boeckaert et al, 2008). On the other hand, P. bryantii has been described as a ruminal bacterium that is involved in oligosaccharolytic and xylanolytic activities (Tajima et al, 2001) and also Prevotella spp.…”
Section: Introductionmentioning
confidence: 99%